Ketersediaan APD, pengetahuan, dan kecemasan perawat di masa pandemi Covid-19 - Riny Apriani; Ambia Ambia (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: The massive spread of Covid-19 caused paralysis in almost all aspects, including the health aspect. In the health sector, nurses are at the forefront of dealing with Covid-19 patients.Purpose: To analyze the relationship between the availability of PPE, knowledge, and anxiety among nurses during the Covid-19 pandemicMethod: This research was conducted from July 2021 to September 2021 at the Madani General Hospital in Medan City. The data used are primary data, the method of collecting data uses the survey method, the population is hospital nurses and the number of samples is 50 nurses as respondents. The analytical method used is Pearson bivariate correlation analysis.Results: Found that there was a negative relationship between the availability of Personal Protective Equipment (PPE) and anxiety with an r coefficient of -0.559 and a significance level (p) of 0.000, and there was a negative relationship between knowledge and anxiety levels with an r coefficient of -0.480 with a significance level (p) of 0.000Conclusion: There is a negative and significant correlation between the availability of personal protective equipment (PPE) and knowledge of the anxiety among nurses during the Covid-19 pandemicSuggestion: Hospital management to provide optimal Personal Protective Equipment and provide information to improve knowledge and reduce the level of anxiety among nurses during the Covid-19 pandemicKeywords: Personal Protective Equipment (PPE); Knowledge; Nurses; Anxiety; Covid-19 pandemic Pendahuluan: Penyebaran Covid-19 yang sangat masif menyebabkan kelumpuhan hampir pada segala aspek termasuk aspek kesehatan. Pada bidang kesehatan, perawat menjadi garda terdepan dalam menangani pasien Covid-19.Tujuan: Untuk menganalisis korelasi antara ketersediaan alat pelindung diri (APD), pengetahuan dan kecemasan perawat di masa pandemi Covid-19Metode: Penelitian ini dilaksanakan pada bulan Juli 2021 sampai dengan September 2021 pada Rumah Sakit Umum Madani di Kota Medan. Data yang digunakan adalah data primer, metode pengumpulan data menggunakan metode survei, menggunakan sampel jenuh, dimana sampel seluruhnya berjumlah 50 perawat sebagai responden.Metode analisis yang digunakan adalah analisis korelasi bivariate pearson.Hasil: Diperoleh bahwa ada hubungan negatif antara ketersediaan Alat Pelindung Diri (APD) terhadap kecemasan dengan koefisien r sebesar -0.559 dan tingkat signifikansi (p) sebesar 0.000, ada hubungan negatif antara pengetahuan dengan tingkat kecemasan dengan koefisien r sebesar -0.480 dengan tingkat signifikasi (p) sebesar 0.000Simpulan: Ada korelasi negatif dan signifikan antara ketersediaan alat pelindung diri (APD) dan pengetahuan terhadap kecemasan perawat di masa pandemi Covid-19Saran: Manajemen rumah sakit untuk menyediakan Alat Pelindung Diri (APD) secara optimal dan memberikan informasi untuk meningkatkan pengetahuan dan mengurangi tingkat kecemasan perawat selama masa pandemi Covid-19